Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/bit.25614
|View full text |Cite
|
Sign up to set email alerts
|

Probing effects of pressure release on virus capture during virus filtration using confocal microscopy

Abstract: Virus filtration is used to ensure drug safety in the production of biotherapeutics. Several recent studies have shown a dramatic decrease in virus retention as a result of a process disruption, e.g., a transient pressure release. In this work, a novel two-label fluorescence technique was developed to probe virus capture within virus filtration membranes using confocal microscopy. Experiments were performed with Ultipor® DV20, Viresolve® Pro, and Viresolve® NFP membranes using bacteriophage φx174 as a model vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“…Recent virus filtration studies have focused on the effects of process parameters on throughput and viral retention. Operating pressure and solution conditions have been identified as crucial parameters for virus retention. Dishari et al indicated that solution pH and ionic strength can alter the electrostatic interactions between viruses and membranes, affecting virus retention .…”
Section: Introductionmentioning
confidence: 99%
“…Recent virus filtration studies have focused on the effects of process parameters on throughput and viral retention. Operating pressure and solution conditions have been identified as crucial parameters for virus retention. Dishari et al indicated that solution pH and ionic strength can alter the electrostatic interactions between viruses and membranes, affecting virus retention .…”
Section: Introductionmentioning
confidence: 99%
“…In large scale biologics manufacturing, depth filters are mostly considered as mechanical entrapment device and little attention is paid to exploit adsorption mechanism for purification advantage. Adsorptive filters have also been studied to provide viral and endotoxin clearance that suggested either electrostatic adsorption or a combination of adsorption and mechanical entrapment (Dishari et al, 2015;Hou & Zaniewski, 1990;Michen et al, 2012;Tipton, Boose, Larsen, Beck, & O Brien, 2002). Adsorptive filters have also been studied to provide viral and endotoxin clearance that suggested either electrostatic adsorption or a combination of adsorption and mechanical entrapment (Dishari et al, 2015;Hou & Zaniewski, 1990;Michen et al, 2012;Tipton, Boose, Larsen, Beck, & O Brien, 2002).…”
mentioning
confidence: 99%
“…Adsorptive filters have also been studied to provide viral and endotoxin clearance that suggested either electrostatic adsorption or a combination of adsorption and mechanical entrapment (Dishari et al, 2015;Hou & Zaniewski, 1990;Michen et al, 2012;Tipton, Boose, Larsen, Beck, & O Brien, 2002). Venkiteshwaran et al (Dishari et al, 2015) has found that porcine parvovirus (PPV) was cleared by X0HC and B1HC depth filters at < 2.5 mS/cm but not at 20 mS/cm, suggesting charge interaction at low conductivity; whereas xenotropic murine leukemia virus (XMuLV) was cleared at high conductivity (20 mS/cm) by X0HC, B1HC, and EKSP, suggesting strong involvement of hydrophobic interactions. It was demonstrated that not only electrostatic interactions but also hydrophobic interactions between the depth filters and DNA molecules played important roles in the adsorptive reduction of DNA.…”
mentioning
confidence: 99%
“…An industry‐wide evaluation of small virus retentive filters also found that large enveloped viruses were reduced below the limit of detection in all 198 cases examined, providing additional rationale that viral testing only needs to be performed with smaller virus as a worst case scenario . It has been shown that virus breakthrough can occur with small virus retentive filters during long processing times . However, proper evaluation and control of process parameters and solution properties can maintain high filter flux and mitigate this risk .…”
Section: Scientific and Technology Considerationsmentioning
confidence: 97%